1985
DOI: 10.2340/0001555565194198
|View full text |Cite
|
Sign up to set email alerts
|

Increased macrophage activity in psoriasis

MS Koh,
BB Majewski,
EL. Rhodes

Abstract: Macrophages derived from circulating blood monocytes of psoriatic patients demonstrated an enhanced release of beta-glucuronidase and lysozyme compared with macrophages from healthy subjects. The relationship of cell activation to the pathogenesis of psoriasis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…137 Marble et al found that the number of macrophages increased in the lesions of psoriasis patients and decreased to non-lesional skin levels after effective treatment with TNF-α inhibitors. 44,138 In another study, Koh et al reported that the activity of macrophages were increased in the lesional skin of patients with psoriasis, 139 suggesting the involvement of macrophages in psoriasis.…”
Section: Dovepressmentioning
confidence: 99%
“…137 Marble et al found that the number of macrophages increased in the lesions of psoriasis patients and decreased to non-lesional skin levels after effective treatment with TNF-α inhibitors. 44,138 In another study, Koh et al reported that the activity of macrophages were increased in the lesional skin of patients with psoriasis, 139 suggesting the involvement of macrophages in psoriasis.…”
Section: Dovepressmentioning
confidence: 99%